Modulation of volatile release and antimicrobial properties of pink pepper essential oil by microencapsulation in single- and double-layer structured matrices - Locali-Pereira, Adilson Roberto [UNESP]; Lopes, Nathalie Almeida [UNESP]; Menis-Henrique, Michele Eliza Cortazzo [UNESP]; Janzantti, Natália Soares [UNESP]; Nicoletti, Vânia Regina [UNESP] (Elsevier, 2020)
The bioactivity of essential oils applied in foods to act as natural preservatives can be reduced due to interactions with other components of the food matrix. Microencapsulation can help to increase the functionality of these compounds. In addition, the electrostatic interaction between proteins and polysaccharides can result in double-layered encapsulating structures, ensuring greater protection to essential oils than using only protein as surface active agent. In this work, pink pepper essential oil was microencapsulated by spray drying of single-layer emulsions, stabilized by soy protein isolate (SPI), and of double-layer emulsions, stabilized by soy protein isolate/high methoxyl pectin (SPI/HMP). Pink pepper essential oil showed predominance of α-pinene, β-pinene, β-mircene, δ-3-carene, D-limonene, and germacrene D. Compared to SPI microcapsules, SPI/HMP microcapsules better preserved the total volatile content identified in pure oil, showed less water adsorption during storage at relative humidity ≥75% and improved antimicrobial properties. When stored for 20 days (25 °C/RH = 52.8%), both microcapsules allowed more gradual release of volatiles compared with non-encapsulated oil. Microencapsulation by spray drying did not have negative effects on the antioxidant activity of the encapsulated oil, as the microcapsules showed similar results to the non-encapsulated oil, around 11 μg Trolox/mg of oil. After storage, however, the non-encapsulated oil showed greater losses of its antioxidant activity due to higher rates of volatile release. In the in vitro antimicrobial activity assay, both microcapsules inhibited growth of Staphylococcus aureus, Bacillus subtilis, Listeria monocytogenes and Listeria innocua, although no inhibition was observed against Gram-negative bacteria. When added in milk, both microcapsules reduced bacterial growth, whereas non-encapsulated oil showed no satisfactory inhibition. Faster reduction of microbial growth in milk was observed for SPI/HMP microcapsules. Inhibition results were better for skim milk than for whole milk, suggesting that the interaction of essential oil with other lipids present in milk decreased its bioactivity. Microencapsulation positively affected the functionality of pink pepper essential oil, highlighting its potential for application as a natural preservative in food products.
Keywords: High methoxyl pectin; Natural preservative; Schinus terebinthifolia Raddi; Sorption isotherms; Soy protein isolate; Terpenes